Metabolic network adaptations in cancer as targets for novel therapies. (24th September 2010) - Cascante, Marta; Benito, Adrian; Zanuy, Miriam; Vizán, Pedro; Marín, Silvia; de Atauri, Pedro
Abstract : Metabolite concentrations and fluxes are the system variables that characterize metabolism. The systematic study of metabolite profiles is known as metabolomics; however, knowledge of the complete set of metabolites may not be enough to predict distinct phenotypes. A complete understanding of metabolic processes requires detailed knowledge of enzyme-controlled intracellular fluxes. These can be estimated through quantitative measurements of metabolites at different times or by analysing the stable isotope patterns obtained after incubation with labelled substrates. We have identified distinct intracellular fluxes associated with metabolic adaptations accompanying cancer. The maintenance of an imbalance between fluxes for the oxidative and non-oxidative PPP (pentose phosphate pathway) has been shown to be critical for angiogenesis and cancer cell survival. Mouse NIH 3T3 cells transformed by different mutated K-ras oncogenes have differential routing of glucose to anaerobic glycolysis, the PPP and the Krebs cycle. These results indicate that knowledge of metabolic fingerprints associated with an altered genetic profile could be exploited in the rational design of new therapies. We conclude that the understanding of the multifactorial nature of metabolic adaptations in cancer may open new ways to develop novel multi-hit antitumoral therapies.